2018
DOI: 10.1016/j.ebiom.2018.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Analysis Reveals a HIF Network and Hub Gene EPAS1 Associated with Lung Adenocarcinoma

Abstract: Recent technological advancements have permitted high-throughput measurement of the human genome, epigenome, metabolome, transcriptome, and proteome at the population level. We hypothesized that subsets of genes identified from omic studies might have closely related biological functions and thus might interact directly at the network level. Therefore, we conducted an integrative analysis of multi-omic datasets of non-small cell lung cancer (NSCLC) to search for association patterns beyond the genome and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 47 publications
1
34
0
Order By: Relevance
“…Nucleus (6) and cytoplasm (8) are another two common sub-cellular locations for the proteins encoded by the genes with transcriptional regulations altered in lung cancers. EPAS1 is known to be a major transcriptional regulator associated with the diagnosis and prognosis of lung cancers (Wang et al, 2018;De Bastiani and Klamt, 2019;Zhang et al, 2019). This study detects that sixteen EPAS1-regulated genes demonstrated quantitatively altered transcriptional regulations in lung cancers.…”
Section: Biological Inferences Of the Detected Transcriptional Regulamentioning
confidence: 80%
“…Nucleus (6) and cytoplasm (8) are another two common sub-cellular locations for the proteins encoded by the genes with transcriptional regulations altered in lung cancers. EPAS1 is known to be a major transcriptional regulator associated with the diagnosis and prognosis of lung cancers (Wang et al, 2018;De Bastiani and Klamt, 2019;Zhang et al, 2019). This study detects that sixteen EPAS1-regulated genes demonstrated quantitatively altered transcriptional regulations in lung cancers.…”
Section: Biological Inferences Of the Detected Transcriptional Regulamentioning
confidence: 80%
“…However, the expression and clinical significance of EPAS1 in NSCLC tissues has not been definitively established. A recent multi‐omics analysis revealed that lung tumor tissues had low EPAS1 mRNA and protein expression compared with normal tissues (Wang et al ., ). In our present study, EPAS1 mRNA expression levels were not correlated with LINC01436 expression levels in lung tumor tissues and no difference was found for EPAS1 protein expression between lung tumor tissues and adjacent normal lung tissues (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…The genotyping data of GWASs of gastric cancer and schizophrenia were deposited in the database of Genotypes and Phenotypes (dbGaP; phs000361 and phs000021, separately). The genotyping data of GWASs of colorectal cancer and lung cancer were derived from previous studies 46,47 .…”
Section: Real Dataset Collectionsmentioning
confidence: 99%